Aktivitas Antioksidan Caulerpa sp. Segar dan Rebus : Antioxidant Activity of Fresh and Boiled Caulerpa sp. - Taufik Hidayat; Nurjanah; Agoes Mardiono Jacoeb; Bagja Adhitia Putera (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2020)
Free radical is a molecule that is highly reactive and unstable, can cause damage to proteins, Deoxyribose Nucleic Acid (DNA), and cell membranes, and can trigger a degenerative diseases. The damages can be prevented by natural or synthetic antioxidant compounds. Caulerpa sp. a green seaweed as a potential source of natural antioxidants. Caulerpa sp. commonly processed into “urap” seaweed in fresh and boiled condition. The boiling process may change the antioxidant activity, so it is necessary to research on the antioxidant activity in Caulerpa sp. fresh and boiled. Extraction method used was a single extraction using methanol p.a for 1×24 hours. Testing of antioxidant activity using DPPH method. Caulerpa sp. fresh and boiled extract has a yield of 8.88% and 6.44%. IC50 values ​​Caulerpa sp. fresh amounted to 452.37±8.29 mg/L and boiled amounted to 484.59±5.69 mg/L. IC50 value category is classified as very weak by 1,1-diphenyl-2-picrylhydrazyl (DPPH) method, so it needs to do another antioxidant activity assay methods and purification of crude extract of Caulerpa sp..